RANCANG BANGUN GAME VIRTUAL REALITY BERTEMA BERBURU BINATANG DENGAN TOKOH PEMANAH BERBASIS ANDROID - Aditya, Muhammad Farid; Basri, Asril (Fakultas Teknik Universitas Persada Indonesia YAI, 2019)
Multimedia allows computer users to get output in a richer and more attractive formcompared to other print or electronic media such as newspapers or radio. The progress of computermultimedia to present information is very visible, because it is presented in the form of multimediaelements such as: sound, text, graphics, video, and animation which are expected to be moreinteractive, so that the information displayed is not only limited to the text model but is combined ofthese multimedia elements, so users are more interested in seeing the information presented.Thepurpose of making this application is to build a Hunting Game application with archers, thisapplication runs stand alone / stand alone, and can not use the network. Application testing is carriedout using the black-box-testing method and the results obtained by the application can run well inaccordance with the functional objectives created. Evaluation of the application of 10 respondentsusing a questionnaire gets very good results with the final results of good valuecalculations.